UV Spectrophotometric Determination of Gefitinib and Rosuvastatin Calcium - Gowri Sankar, D.; Anil Kumar, B.; Joy Babu, P.; Latha, P.V.M. (Asian Journal of Chemistry, 2010)
A simple and sensitive UV spectrophotometric method has been developed for the determination of gefitinib (GFB) and rosuvastatin calcium (RSV) in pure form and pharmaceutical formulations. These methods exhibit maximum absorption (λmax) at 264 nm for GFB and 258 nm for RSV and both the methods obey Beer's law in the concentration range 5-25 μg/mL respectively. The methods are accurate and precise and are extended to pharmaceutical formulations and there was no interference from any common pharmaceutical additives and excipients. The results of the analysis have been validated statistically and by recovery studies.